2009
DOI: 10.1111/j.1365-2966.2009.14968.x
|View full text |Cite
|
Sign up to set email alerts
|

H i content and star formation in the interacting galaxy Arp86

Abstract: We present the results of Giant Metrewave Radio Telescope (GMRT) observations of the interacting system Arp86 in both neutral atomic hydrogen, H I, and in radio continuum at 240 606 and 1394 MHz. In addition to H I emission from the two dominant galaxies, NGC 7752 and NGC 7753, these observations show a complex distribution of H I tails and bridges due to tidal interactions. The regions of highest column density appear related to the recent sites of intense star formation. H I column densities ∼1-1.5 × 10 21 c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…NGC 5996 has been classified as a starburst, and it would be useful to determine its structure with subarcsec resolution to identify any possible active galactic nuclei. It is relevant to note that the dominant galaxy in the Arp 86 system, NGC 7753, which has a high SFR of ∼9 M ⊙ yr −1 , exhibits a flat radio spectrum with α∼0.25 ( S ∝ ν −α ) between 606 and 1394 MHz (Sengupta et al 2009). In the case of M51, although the integrated spectrum is steep between 1415 and 2280 MHz with α∼ 0.87 ± 0.04, the spectrum of the nuclear region is relatively flat with α∼ 0.68 ± 0.01 (Klein, Wielebinski & Beck 1984).…”
Section: Observational Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NGC 5996 has been classified as a starburst, and it would be useful to determine its structure with subarcsec resolution to identify any possible active galactic nuclei. It is relevant to note that the dominant galaxy in the Arp 86 system, NGC 7753, which has a high SFR of ∼9 M ⊙ yr −1 , exhibits a flat radio spectrum with α∼0.25 ( S ∝ ν −α ) between 606 and 1394 MHz (Sengupta et al 2009). In the case of M51, although the integrated spectrum is steep between 1415 and 2280 MHz with α∼ 0.87 ± 0.04, the spectrum of the nuclear region is relatively flat with α∼ 0.68 ± 0.01 (Klein, Wielebinski & Beck 1984).…”
Section: Observational Resultsmentioning
confidence: 99%
“…However, studies of gravitational interactions at optical wavelengths have often focused on major mergers which involve galaxies of similar mass, leading to spectacular structures. Minor mergers with mass ratios in the range of ∼0.1–0.5 may appear less spectacular at optical wavelengths, but show clear and complex signs of interactions in their H i distributions as seen for example in M51 (Rots et al 1990) and Arp 86 (Sengupta, Dwarakanath & Saikia 2009). Although such minor mergers and interactions have so far usually been studied in the nearby Universe, more sensitive H i observations with present and upcoming telescopes should enable us to examine such interactions at higher redshifts and add to our knowledge of galaxy growth and evolution through minor mergers and interactions.…”
Section: Introductionmentioning
confidence: 99%
“…This galaxy is visible in the GALEX UV images (Smith et al, 2007), along with many optical images. Sengupta et al (2009) estimated the stellar mass and H II mass of this galaxy, and found they are 2.9 ×10 9 M ⊙ and 4.5 ×10 8 M ⊙ , respectively. HI column density image shows an connection between NGC 7752 and 2MASX J23470758+2926531 (Sengupta et al, 2009).…”
Section: −1 25mentioning
confidence: 99%
“…Sengupta et al (2009) estimated the stellar mass and H II mass of this galaxy, and found they are 2.9 ×10 9 M ⊙ and 4.5 ×10 8 M ⊙ , respectively. HI column density image shows an connection between NGC 7752 and 2MASX J23470758+2926531 (Sengupta et al, 2009). We also obtained the spectra of 2MASX J23470758+2926531, and found its redshift z = 0.0166 ± 0.0003, similar to Arp 86 (z ∼ 0.0162).…”
Section: −1 25mentioning
confidence: 99%
See 1 more Smart Citation

Once in a blue stream

Martínez-Delgado,
Roca-Fàbrega,
Gil de Paz
et al. 2024
A&A